Immunological Efficiency of Plague Vaccination in the Active Natural Focus. Report 1. Cytokine and immunoglobulin status - K. M. Korytov; V. V. Voitkova; V. I. Dubrovina; A. K. Noskov; A. I. Mishchenko; S. V. Balakhonov (Эпидемиология и вакцинопрофилактика)
Some data of the complex immune status study of humans vaccinated with live plague vaccine EV are represented. These people constantly reside and work at the territory of Gorno-Altai high-mountain natural plague focus that today demonstrates high epidemic activity. It was shown that 93% of the vaccinated humans developed positive seroconversion in 1 month after immunization, but after 6 months the protective antibody titers significantly decreased and did not exceed the diagnostic level. At the same time the revealed changes of the main immunoglobulin concentrations ranged within the physiological norm. Furthermore, increased production of TNF-and IFN- in blood cells in 1 month after vaccination may indicate the development of cellular immune response in humans immunized against plague and confirms the predominant role of cellular response in comparison with humoral reactions.